Challenges for post-Keynesian macroeconomics - Peter Skott (University of Massachusetts, Department of Economics, 2018)
Post-Keynesian macroeconomics faces several challenges. The labor market and the supply side, Örst, have not been getting the attention that they deserve in post-Keynesian growth theory. The failings of the Lucastype ímicroeconomic foundationsí, second, must not lead to a neglect of microeconomic behavior. Convincing macroeconomic theories must recognize and address the connections between macroeconomic relations and the microeconomic behavior whose aggregate manifestation the relations represent. Microeconomic behavior, third, takes place within an institutional structure that shapes economic behavior and economic outcomes. Macroeconomic theory must be both behavioral and structuralist.
Keywords: E12; 330; Neo-Pasinetti theorem; mature economy; induced technical change; autonomous demand; instability; goal orientation